2007
DOI: 10.1063/1.2433768
|View full text |Cite
|
Sign up to set email alerts
|

Broadband SiGe∕Si quantum dot infrared photodetectors

Abstract: The broadband absorption of metal-oxide-semiconductor SiGe/ Si quantum dot infrared photodetectors is demonstrated using boron ␦ doping in the Si spacer. The peak at 3.7-6 m results from the intersubband transition in the SiGe quantum dot layers. The other peak at 6 -16 m mainly comes from the intraband transition in the boron ␦-doping wells in the Si spacers. Since the atmospheric transmission windows are located at 3-5.3 and 7.5-14 m, broadband detection is feasible using this device. The ␦ doping in SiGe qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The operating wavelength range of the device can be varied via the bias voltage. The long-wave responsivity measured at 90 K (approximately 1 mA/W) is higher or comparable to previously reported values for Ge/Si QDIPs [13,14] and SiGe/Si QWIPs [23] at much lower temperatures (10 to 20 K). The proposed device is compatible with the existing Si readout circuitry and suitable for monolithic focal plane array applications.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The operating wavelength range of the device can be varied via the bias voltage. The long-wave responsivity measured at 90 K (approximately 1 mA/W) is higher or comparable to previously reported values for Ge/Si QDIPs [13,14] and SiGe/Si QWIPs [23] at much lower temperatures (10 to 20 K). The proposed device is compatible with the existing Si readout circuitry and suitable for monolithic focal plane array applications.…”
Section: Discussionsupporting
confidence: 86%
“…There are only few works announcing the long-wave operation of detectors based on Ge/Si quantum dots [9,12-14]. Since the long-wavelength photoresponse in this system originates from the bound-to-bound intraband transitions, superior performance of such devices is unlikely, and one is obliged to seek another approach.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the final photocurrent to dark current ratio was increased by three orders. The normalized detectivity ( D * ) was defined as [ 20 ]: where A is the area of the investigated photodetector, and Δ f is the bandwidth of the photodetector. The noise equivalent power (NEP) was formulated as i n /R , where i n is the current noise and R is the responsivity.…”
Section: Mis Uv Photodetectorsmentioning
confidence: 99%
“…indicated that defect-assisted tunneling might help the carrier transport. Although the normalized detectivity of this Al/LPD-SiO 2 /GaN MIS UV photodetector was not given, its detectivity could be estimated as follows: as discussed in [ 20 ], the i n (V ≠ 0) could be approximated as the shot noise (2eI d Δf) 1/2 , where I d was the dark current of the photodetector. Therefore, D *; in Equation (8) could be simplified as: …”
Section: Mis Uv Photodetectorsmentioning
confidence: 99%
“…Although there are issues still to be resolved, possible results on QD-based detectors for terahertz detection have been reported (Su et al, 2006;Huang et al, 2008) recently. Even though the most common material used for QDIPs is the InAs/GaAs (or InGaAs/GaAs) material system, QDIPs are being developed using SiGe/Si (Lin et al, 2007;Tong et al, 2005;Cha et al, 2007) and GaN/ AlN material systems (Doyennette et al, 2006). These could also be of interest for possible terahertz detector development.…”
Section: Terahertz Qd Detectorsmentioning
confidence: 99%